Foreign Direct Investment and the Socio-economic Cohesion of the European Union: Experiences of the New Member Countries - Witkowska, Janina (Comparative Economic Research. Central and Eastern Europe, 2006)
International economic integration can worsen the situation of so called problem regions within the integrated area, i.e. less developed regions or undergoing structural transformation or located in peripheries. The aim of this chapter is to discuss the role of foreign direct investment (FDI) flowing into the new member states in economic and social cohesion of the enlarged Union and to answer a question whether it enhances or impedes the cohesion of the EU. This problem has several aspects and it could be examined at the European, national and regional levels. This chapter focuses on FDI flows into the new member states and their regions, with special reference to Poland, Hungary, the Czech Republic and Slovakia. The enlargement of the EU brought about an unprecedented widening of economic and social disparities within the Union which must be treated as a challenge that the enlarged EU faces. Although the impact of FDI on the socio- economic cohesion of the EU 15 examined at the European level seemed to be limited, the enlarged EU can benefit from FDI inflows stimulating the development of all the new Member States. The impact of FDI on the socio-economic cohesion of the enlarged EU examined at the national and regional levels is controversial. FDI seems to stimulate disparities between regions of the EU and within these regions. FDI tends to be located in the most dynamic regions of host countries which consequently makes catching up processes of lagging regions even more difficult.